Comparative Analysis of CSR Disclosure and Its Impact on Islamic Banks Financial Performance - Riza Aulia Azhary (Al-Azhar Journal of Islamic Economics, 2021)
Corporate Social Responsibility (CSR) is one of the indicators reflecting not only a firm financial performance but also their connection to the stakeholders. This study will analyse the CSR disclosure between two Islamic Banks in MENA Countries; Boubyan Bank from Kuwait and Ithmaar Bank, a Bahrain origin. By employing a mixed qualitative-quantitative method, the paper will contrast both financial reports for 5 consecutive years (2011-2015), and utilise CAMEL rating, as the indicators for financial performance. Furthermore, the data will be analysed intensely using Belal, et al (2015) CSR index. For the non-financial performance, a deeper analysis of the Chairman’s statement will be conducted through text analysis software (DICTION and LIWC). The result showed a consistent output, between financial and non-financial performance, for both banks. Boubyan Bank performed better in terms of financial state, and in addition, avoided impression management procedure. In contrast, Ithmaar Bank indicated the opposite result.